Economic Shocks and Populism: The Political Implications of Reference-Dependent Preferences - Fausto Panunzi; Nicola Pavoni; Guido Tabellini (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper studies electoral competition over redistributive taxes between a safe incumbent and a risky opponent. As in prospect theory, economically disappointed voters bcome risk lovers, and hence are intrinsically attracted by the more risky candidate. We show that, after a large adverse economic shock, the equilibrium can display policy divergence: the more risky candidate proposes lower taxes and is supported by a coalition of very rich and very disappointed voters, while the safe candidate proposes higher taxes. This can explain why new populist parties are often supported by economically dissatisfied voters and yet they run on economic policy platforms of low redistribution. We show that survey data on the German SOEP are consistent with our theoretical predicions on voters' behavior.
Keywords: H00; D70; D90; 330; populism; prospect theory; behavioral political economics